Nutritional properties of pomegranate (Punica granatum) agroindustrial subproducts and their application in fresh pasta (Research, Society and Development, 2025)
The waste food industry generates a large amount and the costs are high, being necessary searches for alternative ways of using these bioproducts. The pasta market is expanding, in addition, it is a food with low cost and low nutritional quality. The objective of this research was to evaluate the influence of the partial replacement of semolina by pomegranate agroindustry residue flour on the physicochemical characteristics of mixed pasta. Pomegranate peel and pulp flours were produced using freeze-drying and a conventional oven as a drying method. Pasta formulations were done by evaluating the relationship of a plant part, drying method and percentage of pomegranate vegetable flour added, tests of antioxidant activity analyses, culinary analysis of the pasta cooking time, the calculation of the percentage of solids loss and yield were done. The freeze-drying process stood out for the quality both peel and pulp flour, the best results was 97,13% of moisture, 6,88% of protein, 11,07% of lipids, 2,32% of ashes, except for the carbohydrate analysis, with 93,65%, based in Tukey`s comparative mean test. The analysis of the technological properties of the masses showed that the lyophilization process reduced the loss of solids and the conventional oven process increased the yield for both parts of the plant. In the form of flour, all showed antioxidant activity, but after being added to pasta, only the one made with flour from the husk maintained this activity. Therefore, the pomegranate bioproduct proved to be a potential input for the development of pasta, aiming at nutritional and functional improvement.